2019
DOI: 10.5267/j.msl.2019.5.011
|View full text |Cite
|
Sign up to set email alerts
|

The influence of total quality management toward organization performance

Abstract: This study is primarily focused on the effect of total quality management (TQM) on organization performance of Small and Medium Enterprises (SMEs) service sector in Selangor, Malaysia. The four critical elements of TQM; namely customer focus (X1), continuous improvement (X2), strategically based (X3), and total employee involvement (X4) are used as an important factors influencing on organization performance (Y). The necessary data are collected from 350 managers/owners of service sector SMEs in Selangor, Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 9 publications
6
93
0
23
Order By: Relevance
“…Chatzoudes and Chatzoglou (2015) used dimensions of supply chain performance (SCP), customer satisfaction and financial performance. Pambreni et al (2019) used indicators of organization performance including financial performance, internal or operational performance, customer satisfaction. According to Sofyalogğlu and Oztürk (2012), general performance measurement is divided into two sub-dimensions, they are business performance and operational performance.…”
Section: Performancementioning
confidence: 99%
“…Chatzoudes and Chatzoglou (2015) used dimensions of supply chain performance (SCP), customer satisfaction and financial performance. Pambreni et al (2019) used indicators of organization performance including financial performance, internal or operational performance, customer satisfaction. According to Sofyalogğlu and Oztürk (2012), general performance measurement is divided into two sub-dimensions, they are business performance and operational performance.…”
Section: Performancementioning
confidence: 99%
“…In it, a management system is a collection of interrelated or interacting elements to set policies and goals and to achieve those goals. Quality orientation and management include quality policy setting and quality objectives, quality planning, quality management, quality assurance and quality improvement (Pambreni et al, 2019).…”
Section: The Effectiveness Of Qms In Accordance With Iso 9001mentioning
confidence: 99%
“…org 2019). Gotzamani et al, 2006(as cited in Singh, 2011 has identified 11 key enabling factors from his analysis that impacts on the success of total quality management system in SMEs and established a framework for improving the performance and customer satisfaction, in conjunction with Pambreni et al (2019) who concluded customer focus, continuous improvement, total employee involvement. Strategically based together, these are influencing factors for organization performance up to 40% while the rest are impacted by other factors that are not studied from his work.…”
Section: Total Quality Management System and Smes Performancementioning
confidence: 99%